2021
DOI: 10.1155/2021/6661867
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Increasing the Permeability of Water-Bearing Coal Rock by Microwave Steam Explosion

Abstract: Microwave heating of water-bearing coal can promote pore water evaporation. The pores are broken under the action of steam pressure, increasing the permeability of the coal. This study is aimed at investigating the mechanism of permeability improvement of water-bearing coal rock by microwave steam explosion. First, a microwave oven was used to irradiate and heat five groups of coal rock with different water contents; the NMR test was then conducted on the heated sample. Second, the internal vapor pressure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Local tensile stress was formed by the expanding volume in the pores and cracks of the coal, which promoted the formation and propagation of cracks. , Some cracks were interconnected to form a crack network leading to contact with the external environment. Hence, the water vapor in the coal was ejected along the crack, resulting in a microwave heating effect that was similar to a “steam explosion” (see Figure b). This led to the exponential change of the coal sample mass with increased microwave intensity (see Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Local tensile stress was formed by the expanding volume in the pores and cracks of the coal, which promoted the formation and propagation of cracks. , Some cracks were interconnected to form a crack network leading to contact with the external environment. Hence, the water vapor in the coal was ejected along the crack, resulting in a microwave heating effect that was similar to a “steam explosion” (see Figure b). This led to the exponential change of the coal sample mass with increased microwave intensity (see Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…We have also previously shown that the water contained in coal rocks can be quickly heated under microwave irradiation. The water vapor that is formed in this process exerts a high pressure on the inner wall of the pores, eventually destroying the pore structure and increasing the connectivity [25]. Figure 1 displays the macro-and microprocesses of explosion caused by water vapor contained in the coal; of course, in the process of microwave heating, the cracks in the coal are not only caused by steam pressure but also caused by the imbalance of the thermal stress, the thermal decomposition of natural filler, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental measure to improve the gas extraction rate is to create a large-scale fracture network in the coal seam to provide pressure relief space for the coal seam and gas drainage and migration channels, subsequently increasing the permeability of the coal seam (Bai et al, 2017;Qi et al, 2021). In recent years, relevant experts and scholars at home and abroad have carried out a large number of theoretical analyses, laboratory experiments, numerical simulations, similar simulations, and engineering experiments to improve coal seam permeability.…”
Section: Introductionmentioning
confidence: 99%